2003
DOI: 10.1143/jpsj.72.29
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Excitations outside the Vortex Cores in MgB2Probed by Muon Spin Rotation

Abstract: The magnetic penetration depth λ in the mixed state of MgB2 has been determined microscopically from the field distribution around magnetic vortices probed by muon spin rotation. Both the temperature and magnetic field dependence of λ strongly suggest the presence of delocalized quasiparticles around the vortex cores. In particular, the effect of Doppler shift has been clearly observed as a finite gradient of the field dependence of λ, strongly suggesting an anisotropic order parameter with the region of a van… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
43
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 35 publications
8
43
0
Order By: Relevance
“…On the other hand, we note that there are at least six low-T experiments showing or at least suggesting power-law behaviors which seem to indicate gap nodes (Panagopoulos et al 2001, Zhukov et al 2001, Pronin et al 2001, Ohishi et al 2003. [Admittedly, the lowest temperatures in some of these experiments are too high to be convincing.…”
mentioning
confidence: 76%
“…On the other hand, we note that there are at least six low-T experiments showing or at least suggesting power-law behaviors which seem to indicate gap nodes (Panagopoulos et al 2001, Zhukov et al 2001, Pronin et al 2001, Ohishi et al 2003. [Admittedly, the lowest temperatures in some of these experiments are too high to be convincing.…”
mentioning
confidence: 76%
“…Besides this, it has turned out that MgB 2 exhibits η = 1.27 at 0.26T c . 22 In this case, it is suggested that the presence of two superconducting energy gaps, one being relatively small (∼1 meV), is responsible for the field dependence of λ eff observed at a finite temperature. In this sense, we cannot exclude the multiple-gap scenario in KOs 2 O 6 , since the measurement was performed at a finite temperature of 2 K. The present result suggests the presence of a small energy gap having a magnitude of less than ∼0.2 meV in the multiple-gap scenario.…”
Section: /8mentioning
confidence: 96%
“…We examined the consistency of our data with the ARPES result by employing a phenomenological doublegap model with s-wave symmetry, 28,29) s ðTÞ ¼ ð0Þ À w Á ðÁ 1 ; TÞ À ð1 À wÞ Á ðÁ 2 ; TÞ; ðÁ; TÞ ¼ 2ð0Þ…”
mentioning
confidence: 97%